Effect of Tabata Methods as Interval Training Variant on Physical Performance of Pedagogical University Students - С. А. Пашкевич; Н. І. Бондаренко; Г. Л. Нікуліна (OVS LLC, 2015)
The objective of the research is to develop, substantiate and evaluate the effectiveness of interval training methods during physical training of students of higher educational institutions pursuant to changes in physical performance. Methods.  The reference group (RG) consisted of 20 students (5 male and 15 female), the test group (TG) - 26 (5 male and 19 female). The RG students did fitness during their physical training classes at the university, while the TG students, besides the same program, did Tabata training in class and independently on their own at three levels of intensity four times a week for four weeks. We evaluated the effectiveness by the changes in students' physical performance. We used χ2 tests (binary variables) to compare the output characteristics in the groups, t-tests (continuous variables) and Mann-Whitney test to compare the distribution of ordinal variables, and Wilcoxon test (related samples). Results. During the month of the forming experiment being conducted, the TG students' physical performance showed the increase of + 38.9% and was reliably different from the results of the initial period (p < 0.05). The anthropometric indicators did not significantly change in their dynamics, nor was there any difference between the comparison groups. The evaluation of the effectiveness of interval training by the Tabata methods pursuant to the dynamics of the students' physical performance allowed to objectively prove the positive effect that additional independent training of students has when implemented.